The action effect was not affected by cognitive load - Zhao, Guang; Duan, Yuhao; Wang, Hanxu; Wu, Rongtao; Zhang, Jichao (Frontiers in Neuroscience, 2025)
IntroductionActions are traditionally thought to be guided by cognition. A reverse pathway where action influences perception has been revealed through the “action effect”. The action effect refers to the acceleration of target search when targets share features with previously acted-upon stimuli.MethodsIn this study, to further understand its cognitive mechanism, we investigated whether the action effect is modulated by cognitive load. Participants were instructed to press a key if the prime stimulus (a colored color word) matched a specified color. Otherwise, they were instructed to passively view the prime. The color of the prime was either congruent (no cognitive load) or incongruent (cognitive load) with its semantic meaning. The magnitude of the action effect between the two conditions was compared. Using EEG technology, we addressed the research gap concerning the neural mechanisms underlying the action effect.ResultsBehaviorally, response times were shorter in the action condition compared to the no-action condition, confirming the presence of the action effect. Notably, the magnitude of the action effect was equivalent between the congruence and incongruence conditions. Electrophysiological data revealed that attentional priority for acted-on stimuli was enhanced, while the response selection process was delayed. Importantly, all neural markers—including N2pc, P300b, and late LPC—exhibited minimal differences between the congruent and incongruent conditions.DiscussionThe findings provide robust evidence that the action effect remains intact in the presence of cognitive load. This not only advances our understanding of its underlying mechanisms but also provides theoretical guidance for its potential application conditions.